Studies of Physio-chemical characteristics and sediment environment along the coastal waters Pulau Tuba, Langkawi - Khan Chowdhury, Ahmed Jalal; Nordin, Noor Faizul Hadry; Yunus, Kamaruzzaman; Hashim, Ridzwan; Saad, Shahbudin; Alam, Md. Zahangir (IIUM Press, 2009)
Field observations on physico-chemical characteristics of waters and sediment quality were carried out from March, 2005 to Dec, 2005 at different stations (station 1 - Main Jetty Pulau Tuba, Station 2 - Simpang Tiga Mangrove Area, Station 3 - Aquaculture Area Pulau Tuba and Station 4 - Kuah Jetty) along the coastal waters of Pulau Tuba Langkawi. The physico-chemical parameters such as temperature (27.43-28.88°C), DO (3.79-6.49 mg/l), pH (7.72-8.20), salinity (33.10-33.96 ppt), TDS (32.27-32.77) g/l) and specific conductivity (49.83-51.63 mS/cm) of all the stations did not show much variations among the stations. While Nitrate, Nitrite and Phosphrate among the stations were found varied and ranged 2.04-26.93 µg at N/l and 0.27 - 1.33 µg at P/l respectively. Although the textures of the bottom sediment were limited to sand, silt and clay, but most of the stations were dominated by black clay. The highest amount clay (82.87%) was found at station 4. The amount of organic carbon in the sediment ranged from 1.92-3.0%. The highest amount of Fe (366.90µg/g) was found in station 4. While Mn (39.75µg/g) and Pb (3.15µg/g was found in stations 3 and 1 respectively. The results showed that there were no significant differences (P>0.05) among the physico-chemical profile of the different stations, while the heavy metals and nutrients showed significant differences (P<0.05) among the stations. Although the station 4 was the most man induced polluted area due to the dumping zone of the waste materials round the year. Nevertheless, all the sampling areas should be given utmost importance for the habitat of the aquatic organisms in the near future.